Accountability in Green Waqf Management in Support of the Sustainable Development Goals (SDGs): A Study of Miftahul Ulum Islamic Boarding School - Syafiq Febriyanto; Robiatul Auliyah; Maulida Fitria; Merie Satya Angraini (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the accountability of green waqf management at Miftahul Ulum Islamic Boarding School from the perspective of the Sustainable Development Goals (SDGs). The study is motivated by the importance of strengthening accountability to achieve transparent, professional, and sustainable waqf governance. This research employed a qualitative method with a case study approach through in-depth interviews, observations, and documentation involving waqf administrators at the Islamic boarding school. The findings reveal that the implementation of green waqf at Miftahul Ulum Islamic Boarding School contributes significantly to the achievement of the SDGs, particularly No Poverty (SDGs 1), Zero Hunger (SDGs 2), Quality Education (SDGs 4), and Clean Water and Sanitation (SDGs 6). However, the accountability system remains traditional and centered on the Kiai as the highest authority, with accountability mechanisms that are largely internal and trust-based. Limited formal documentation, written reporting, and asset legalization remain major challenges in establishing professional and modern waqf governance. This study recommends strengthening the capacity of nadzir, implementing digital reporting systems, and enhancing collaboration with relevant institutions to integrate sharia accountability principles and environmental sustainability in the management of green waqf in Islamic boarding schools.